How to Teach Short Story Writing With Analogy? - Zulfa Fahmy; Diyamon Prasandha; Titi Wuryani (Conference on the Environmental Conservation through Language, Arts, Culture and Education, 2023)
Teaching writing short stories is not an easy thing for most teachers. Teaching writing short stories requires perseverance to explain complex concepts understood. The concepts of short story writing are abstract, so students feel difficult to understand and apply them in writing activities. Analogy appears as a solution to these problems. This reasoning model makes it easier for students to understand abstract concepts. Therefore, a simple analogy analogy is needed to explain complex concepts. Learning using this analogy is designed to be easy to understand. The analogy is a short story builder element. In this way, students will no longer have difficulties in writing short stories